High kicks, hot chocolate, and homicides - McHugh, Mary (McHugh, Mary. Happy Hoofers mystery., 2016)
"It's a Christmas miracle for the Happy Hoofers--Tina, Janice, Pat, Mary Louise, and Gini. They've scored a gig at New York City's Radio City Music Hall with the legendary Rockettes, complete with sexy Santa suits and microphones on their shoes. But when a dazzling diva of a dancer is found dead under the stage, there's quite a lineup of suspects. In between rehearsals and seasonal sightseeing--and the discovery of a multi-talented, multi-colored cat--the toe-tapping troupe has to sort out the intrigue before another victim kicks the bucket..." --